Paleobiology of Titanosaurs: reproduction, development, histology, pneumaticity, locomotion and neuroanatomy from the South American fossil record - Garcia, Rodolfo Andres (2015)
Much of the current paleobiological knowledge on titanosaur sauropods was attained in just the last fifteen years, in particular that related to reproductive and developmental biology. Recent years have also seen progress on other poorly explored topics, such as pneumaticity, muscle architecture and locomotion, and endocast reconstruction and associated structures. Some titanosaurs laid numerous, relatively small Megaloolithidae eggs (with diameters ranging from 12 to 14 cm) in nests dug In the ground and, as known from the South American records, probably eggs of the multispherulitic morphotype. During ontogeny, certain titanosaurs displayed some variations in cranial morphology, some of them likely associated with the differing feeding habits between hatchlings and adults. The bone tissue of some adult titanosaurs was rapidly and cyclically deposited and shows a greater degree of remodeling than in other sauropods. Saltasaurines in particular show evidence of postcranial skeletal pneumaticity in both axial and appendicular skeleton, providing clues about soft tissue anatomy and the structure of the respiratory system. Titanosaurs, like all sauropods, were characterized by being fully quadrupedal, although some appendicular features and putative trackways indicate that their stance was not as columnar as in other sauropods. These anatomical peculiarities are significantly developed In saltasaurines, a derived group of titanosaurs. Compared with other sauropods, some titanosaurs seem to have had very poor olfaction but would have been capable of capturing sounds In a relatively wide range of high frequencies, although not to the extent of living birds.